Blood group detection using image processing techniques - Rahman, Sakib; Rahman, Md. Atifur; Khan, Fariha Ashraf; Shahjahan, Shabiba Binte; Nahar, Khairun (BRAC University, 2018)
Cataloged from PDF version of thesis report.